Haemophilus parasuis Subunit Vaccines Based on Native Proteins with Affinity to Porcine Transferrin Prevent the Expression of Proinflammatory Chemokines and Cytokines in Pigs - R. Frandoloso; S. Martínez-Martínez; E. F. Rodríguez-Ferri; S. Yubero; D. Rodríguez-Lázaro; M. Hernández; C. B. Gutiérrez-Martín (Clinical and Developmental Immunology)
The expression of chemokines (CCL-2 and CXCL-8) and cytokines (IL-1α, IL-1β, IL-6, TNF-α, and IL-10) was evaluated by RT-qPCR in colostrum-deprived pigs vaccinated and challenged with Haemophilus parasuis serovar 5. Two vaccines containing native proteins with affinity to porcine transferrin (NPAPTim and NPAPTit) were tested, along with two control groups: one inoculated with PBS instead of antigen (challenge group (CHG)), and another one nonimmunized and noninfected (blank group). The use of NPAPTim and NPAPTit resulted in complete protection against H. parasuis (no clinical signs and/or lesions), and both vaccines were capable of avoiding the expression of the proinflammatory molecules to levels similar to physiological values in blank group. However, overexpression of all proinflammatory molecules was observed in CHG group, mainly in the target infection tissues (brain, lungs, and spleen). High expression of CCL-2, CXCL-8, IL-1α, IL-1β, and IL-6 can be considered one of the characteristics of H. parasuis infection by serovar 5.